Imaging Findings in MR Imaging–Guided Focused Ultrasound Treatment for Patients with Essential Tremor - Wintermark, M.; Druzgal, J.; Huss, D.S.; Khaled, M.A.; Monteith, S.; Raghavan, P.; Huerta, T.; Schweickert, L.C.; Burkholder, B.; Loomba, J.J.; Zadicario, E.; Qiao, Y.; et al. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: MR imaging–guided focused sonography surgery is a new stereotactic technique that uses high-intensity focused sonography to heat and ablate tissue. The goal of this study was to describe MR imaging findings pre- and post-ventralis intermedius nucleus lesioning by MR imaging–guided focused sonography as a treatment for essential tremor and to determine whether there was an association between these imaging features and the clinical response to MR imaging–guided focused sonography. MATERIALS AND METHODS: Fifteen patients with medication-refractory essential tremor prospectively gave consent; were enrolled in a single-site, FDA-approved pilot clinical trial; and were treated with transcranial MR imaging–guided focused sonography. MR imaging studies were obtained on a 3T scanner before the procedure and 24 hours, 1 week, 1 month, and 3 months following the procedure. RESULTS: On T2-weighted imaging, 3 time-dependent concentric zones were seen at the site of the focal spot. The inner 2 zones showed reduced ADC values at 24 hours in all patients except one. Diffusion had pseudonormalized by 1 month in all patients, when the cavity collapsed. Very mild postcontrast enhancement was seen at 24 hours and again at 1 month after MR imaging–guided focused sonography. The total lesion size and clinical response evolved inversely compared with each other (coefficient of correlation = 0.29, P value = .02). CONCLUSIONS: MR imaging–guided focused sonography can accurately ablate a precisely delineated target, with typical imaging findings seen in the days, weeks, and months following the treatment. Tremor control was optimal early when the lesion size and perilesional edema were maximal and was less later when the perilesional edema had resolved. CRSTClinical Rating Scale for TremorVimventralis intermedius nucleus